Public Green Open Space (RTH) Management in Kambangan Village Lebaksiu District, Tegal Regency - Khaq, M. Zimamul (Library of Sultan Agung Islamic University, 2024)
This study aimed to determine the function of the construction of Green Open Space in Kambangan Village, Lebaksiu District, Tegal Regency. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and literature and documentation studies using Eckersley's Good Environmental Governance theory.The results showed that 1). The existence of Green Open Space (RTH) in Kambangan village is able to create a green and clean environment and can also create a large economic impact where the creation of new MSMEs for the Kambangan village community itself, besides that it is also a sports center for the Kambangan village community and its surroundings without setting aside environmental issues. 2). Public and third-party awareness (traders/markets) to actively participate in the Green Open Space program is still low. There is a refusal from some traders to move their stalls to the new location around the RTH because there is no guarantee of crowds from the Village Government. Keywords: Green Open Space; Village Government